Strucchange: An R package for testing for structural change in linear regression models - Achim Zeileis; Friedrich Leisch; Kurt Hornik; Christian Kleiber (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2001)
This paper introduces ideas and methods for testing for structural change in linear regression models and presents how these have been realized in an R package called strucchange. It features tests from the generalized uctuation test framework as well as from the F test (Chow test) framework. Extending standard signi_cance tests it contains methods to _t, plot and test empirical uctuation processes (like CUSUM, MOSUM and estimatesbased processes) on the one hand and to compute, plot and test sequences of F statistics with the supF, aveF and expF test on the other. Thus, it makes powerful tools available to display information about structural changes in regression relationships and to assess their signi_cance. Furthermore it is described how incoming data can be monitored online.
Keywords: 519; structural change; CUSUM; MOSUM; recursive estimates; moving estimates; online monitoring; R; S